Editorial - Deniz EVCİK, (Archives of Rheumatology, 2011)
Dear Readers Now we are pleased to introduce you to the September issue of the Turkish Journal of Rheumatology (TJR). In this issue we have interesting, original articles and case reports. It is our pleasure to thank all our contributers and Bayçınar Medical Publishing. In 2010, recommendations for the management of ankylosing spondylitis have been revised by the collaboration of an ASAS international study group and EULAR. This study was conducted to develop our national recommendations for Turkish physicians. Therefore, under the umbrella of TLAR, a study group composed and worked on the management of recommendations by considering the facts pertinent to conditions in Turkey. In this issue it is our pleasure to introduce you the “TLAR National Recommendations for the management of ankylosing spondylitis”. We hope this guideline will be very useful for every physician dealing with rheumatology, particularly the specialists in physical medicine and rehabilitation and rheumatology in Turkey. An appendix, including the items written in Turkish, is at the end of the study. Also, the Turkish translation of the article will be readily available on our website (www.trasd.org.tr). I also want to inform you that the national recommendations for the management of rheumatoid arthritis and osteoarthritis have been developed and will be published in upcoming issues. With my best regards Prof. Dr. Deniz Evcik Editor